Cochlear Implantation in Children With Autism Spectrum Disorder. Issue 8 (September 2015) - Eshraghi, Adrien A.; Nazarian, Ronen; Telischi, Fred F.; Martinez, Diane; Hodges, Annelle; Velandia, Sandra; Cejas-Cruz, Ivette; Balkany, Thomas J.; Lo, Kaming; Lang, Dustin
Abstract : Objective: To assess the outcome of cochlear implantation in children with autism spectrum disorder (ASD). Study Design: Retrospective case review and survey. Setting: Tertiary referral center. Patients: Children who meet criteria for cochlear implantation and diagnosis of ASD. Main Outcome Measures: Receptive and expressive language scores and parental survey data. Results: Fifteen patients with history of ASD and cochlear implantation were analyzed and compared with 15 patients who received cochlear implant and have no other disability. Postoperatively, more than 67% of children with ASD significantly improved their speech perception skills, and 60% significantly improved their speech expression skills, whereas all patients in the control group showed significant improvement in both aspects. The top 3 reported improvements after cochlear implantation were name recognition, response to verbal requests, and enjoyment of music. Of all behavioral aspects, the use of eye contact was the least improved. Survey results in regard to improvements in patient interaction were more subtle when compared with those related to sound and speech perception. The most improved aspects in the ASD patients' lives after cochlear implantation seemed to be attending to other people's requests and conforming to family routines. Of note, awareness of the child's environment is the most highly ranked improvement attributed to the cochlear implant. Conclusion: Cochlear implants are effective and beneficial for hearing impaired members of the ASD population, although development of language may lag behind that of implanted children with no additional disabilities. Significant speech perception and overall behavior improvement are noted.